2010
DOI: 10.1111/j.1745-9133.2010.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Is problem‐oriented policing effective in reducing crime and disorder?

Abstract: Research Summary We conducted a Campbell systematic review to examine the effectiveness of problem‐oriented policing (POP) in reducing crime and disorder. After an exhaustive search strategy that identified more than 5,500 articles and reports, we found only ten methodologically rigorous evaluations that met our inclusion criteria. Using meta‐analytic techniques, we found an overall modest but statistically significant impact of POP on crime and disorder. We also report on our analysis of pre/post comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
186
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(196 citation statements)
references
References 49 publications
8
186
0
2
Order By: Relevance
“…To address these questions, a related literature that is found mostly in criminology has studied the effect of changes in the intensity of policing on crime with a distinct focus on the crime-reducing effect of various "best practices." In particular, declines in crime that are not attributable to spatial displacement have been linked to the adoption of "hot spots" policing (Sherman and Rogan 1995, Sherman and Weisburd 1995, Braga 2001, Braga 2005, Weisburd 2005, Braga and Bond 2008, and Berk and MacDonald 2010, "problem-oriented" policing (Braga et al 1999;Braga et al 2001;and Weisburd et al 2010), and a variety of other proactive approaches. Similarly, a large research literature that has examined the local impact of police crackdowns has consistently found large and immediate (but typically not lasting) reductions in crime in the aftermath of hyper-intensive policing (Sherman 1990).…”
Section: Police Deployment and Tacticsmentioning
confidence: 99%
“…To address these questions, a related literature that is found mostly in criminology has studied the effect of changes in the intensity of policing on crime with a distinct focus on the crime-reducing effect of various "best practices." In particular, declines in crime that are not attributable to spatial displacement have been linked to the adoption of "hot spots" policing (Sherman and Rogan 1995, Sherman and Weisburd 1995, Braga 2001, Braga 2005, Weisburd 2005, Braga and Bond 2008, and Berk and MacDonald 2010, "problem-oriented" policing (Braga et al 1999;Braga et al 2001;and Weisburd et al 2010), and a variety of other proactive approaches. Similarly, a large research literature that has examined the local impact of police crackdowns has consistently found large and immediate (but typically not lasting) reductions in crime in the aftermath of hyper-intensive policing (Sherman 1990).…”
Section: Police Deployment and Tacticsmentioning
confidence: 99%
“…6 In a randomized trial involving Jersey City, New Jersey, Braga et al (1999) identified 24 Experiment (Weisburd and Green, 1995) provides more direct support for the added benefit of the application of problem solving approaches in hot-spot policing (Weisburd et al, 2010). In this study, a similar number of narcotics detectives were assigned to treatment and control hot spots.…”
Section: Police Strategies To Preventmentioning
confidence: 92%
“…We acknowledge that there is some controversy surrounding some aspects of this metric, such as whether the computed statistic is in fact a risk ratio or an odds ratio, 6 and whether it sufficiently deals with over-dispersion in the data (see Marchant, 2004Marchant, , 2005. To address this, we use an approach adopted elsewhere (Farrington et al, 2007;Weisburd, Telep, Hinkle, & Eck, 2008) of multiplying the standard error by an inflation factor (IF, in this case two) when calculating confidence intervals.…”
Section: Quantitative Data Analysismentioning
confidence: 99%